SWIRL FLUID FLOW NOZZLE: A SOLUTION FOR FLUID JET POLISHING PROCESS - Najib, A.M.; Waechter, D. (Journal of Advanced Manufacturing Technology (JAMT), 2021)
The Fluid Jet Polishing is one of emerging technology for fabrication of precision optics and medical implants. The current sub-aperture fluid jet polishing uses a canonical shaped nozzle which produces inequalities of surface removal. This study aims to present an alternative method using swirl nozzle design in order to eliminate the disadvantage of a ring-shaped influence function resulting from the fluid jet polishing using the conventional conical nozzle. The fluid jet flow of the conventional nozzle and swirl flow nozzle were investigated using numerical simulation. The jet profile and its parameter near the impact wall constitute a significant point of interest. The results indicated that particles and fluid exiting the nozzle at circumferential velocity improve the material removal characteristics during the polishing process. The study concluded that the nozzle with swirl flow resulted in a bell-shaped velocity profile near the impact wall, which provide a significant improvement in the polishing process using the fluid jet.